Pheochromocytoma of the urinary bladder – A case report - Marić, Predrag; Milović, Novak; Bančević, Vladimir; Košević, Branko; Aleksić, Predrag; Kuzmić Janković, Snežana; Hajduković, Zoran; Milev, Boško; Cerović, Snežana (Vojnosanitetski pregled, 2017)
Introduction. Pheochromocytoma of the urinary bladder is a rare tumor and presents less than 0.06% of all urinary bladder tumors. Case report. We presented a 49-year-old female patient with a history of daily paroxysmal hypertension accompanied with flushing of the face and upper chest, palpitations and excessive sweating prior to micturition. Ultrasonography reported a 3 cm bladder wall tumor. The 131I-metaiodobenzylguanidine (131I-MIBG) scan showed a pathological isotope accumulation in the projection of the bladder. The patient underwent a partial cystectomy. One year following the operation the patient was normotensive and without recurrence. Conclusion. The most efficient treatment option for bladder pheochromocytoma is surgical resection. The most important fact in the diagnostics is suspicion on this rare condition.
Keywords: pneochromocytoma; urinary bladder neoplasms; ultrasonography; radionuclide imaging; urologic surgical procedures